2020
DOI: 10.14421/ijid.2020.09205
|View full text |Cite
|
Sign up to set email alerts
|

Public Sentiments Analysis about Indonesian Social Insurance Administration Organization on Twitter

Abstract: Insurance Administration Organization, which can be used by all people. However, this organization has received various criticisms from the public through social media, namely Twitter. This study aims to analyze public sentiment about the Indonesian Social Insurance Administration Organization on Twitter. The method used in this research is the Naive Bayes Classifier (NBC) method and uses the Support Vector Machine (SVM) method as a comparison. The amount of data used was 12,990 tweets with a data collection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…After the classification model is formed in the training process, the classification process is performed [15]. The research stages are shown in Figure 1.…”
Section: A Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…After the classification model is formed in the training process, the classification process is performed [15]. The research stages are shown in Figure 1.…”
Section: A Modelmentioning
confidence: 99%
“…A naive Bayes classifier is a classification method based on Bayes' theorem. This classifier assumes that the presence of features within a class is independent of other features [15]. Equation ( 1) is a Bayesian formula.…”
Section: Data Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…There has already been study done on the Indonesian Social Insurance Administration Organization, such as research on the Public Sentiments Analysis of the Indonesian Social Insurance Administration Organization using Twitter data [2]- [4]. Furthermore, the lexicon-based method is a feature extraction method that has the potential to increase system performance.…”
Section: Abstract a Rt I C L E I N F Omentioning
confidence: 99%
“…Research [8] is the development of an application to classify comments about recipes from one of the popular food community sites into positive or negative sentiments. Another research is to analyze sentiment regarding the services of the Social Security Administrative Body (BPJS) for Health in Indonesia [9]. This study analyzes tweet sentiment about BPJS services into 4 sentiment classifications, namely satisfied, disappointed, happy and sad.…”
Section: Introductionmentioning
confidence: 99%